Identification of pancreatic cancer-specific protease substrates for protease-dependent targeted delivery - Etienne J. Slapak; Danny A. Zwijnenburg; Jan Koster; Maarten F. Bijlsma; C. Arnold Spek (Oncogenesis)
Abstract Pancreatic ductal adenocarcinoma (PDAC) presents significant challenges due to the inadequacy of existing chemotherapeutics, which often result in toxicity-dependent dose limitations and premature cessation of therapy. Targeted delivery of therapeutic molecules offers a promising solution. Given that PDAC is marked by a desmoplastic reaction with extensive aberrant protease activity, protease-dependent targeted delivery could minimize off-target toxicities and is of increasing interest. The efficacy of targeted delivery hinges on the specificity of the substrates used; insufficient specificity can lead to off-target effects, reducing the advantage over non-targeted methods. Here, we employ an unbiased library approach to screen over 7 million peptide substrates for proteolytic cleavage by PDAC cell lysates, identifying 37 substrates enriched by at least 500-fold after three rounds of selection. As systemically administered targeted delivery depends on the absence of substrate cleavage in circulation, the peptide library was also screened against whole blood lysates, and enriched substrates were removed from the PDAC-enriched dataset to obtain PDAC-specific substrates. In vitro validation using FRET-peptides showed that 13 of the selected 15 substrates are cleaved by a panel of PDAC cell line lysates. Moreover, evaluation against healthy murine organ and human blood lysates to assess off-target cleavage revealed that the identified substrates are indeed PDAC-specific and that several substrates may be superior with respect to PDAC specificity over the CAPN2-responsive substrate, which has recently shown preclinical potential in targeted therapy, but future animal models should address the potential superiority. Overall, we thus identified substrates with high selectivity and sensitivity for PDAC that could be employed in protease-dependent targeted therapies.